2018
DOI: 10.1155/2018/7859601
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Mechanism of CAY10683 on Intestinal Mucosal Barrier in Acute Liver Failure through LPS/TLR4/MyD88 Pathway

Abstract: The purpose of this study was to investigate the protective mechanism of HDAC2 inhibitor CAY10683 on intestinal mucosal barrier in acute liver failure (ALF). In order to establish ALF-induced intestinal epithelial barrier disruption models, D-galactosamine/LPS and LPS were, respectively, used with rats and NCM460 cell and then administrated with CAY10683. Transepithelial electrical resistance (TEER) was measured to detect the permeability of cells. Real-time PCR and Western blotting were employed to detect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…These results are consistent with our previous findings that TSA can effectively inhibit the release of multiple inflammatory factors, improve hepatocyte injury, and improve the survival rate of rats with acute-on-chronic liver failure [16]. The HDAC2 inhibitor CAY10683 achieves the goal of treating acute liver failure by protecting the damaged intestinal mucosa and reducing intestinal endotoxemia [17]. Most of these studies are based on the mechanism association with acetylation in the process of inflammation.…”
Section: Introductionsupporting
confidence: 90%
“…These results are consistent with our previous findings that TSA can effectively inhibit the release of multiple inflammatory factors, improve hepatocyte injury, and improve the survival rate of rats with acute-on-chronic liver failure [16]. The HDAC2 inhibitor CAY10683 achieves the goal of treating acute liver failure by protecting the damaged intestinal mucosa and reducing intestinal endotoxemia [17]. Most of these studies are based on the mechanism association with acetylation in the process of inflammation.…”
Section: Introductionsupporting
confidence: 90%
“…LPS was used to induce damage to the mucosal barrier of NCM460 cells. The NCM460 cells treated with the HDAC2 inhibitor (CAY10683) increased mRNA and protein levels of ZO-1 (Wang et al, 2018). Collectively, this suggests that HDAC2 plays differential roles in the increase or reduction of epithelial barrier integrity depending on the site of the human epithelial cells.…”
Section: Histone Deacetylases (Hdacs) In Armentioning
confidence: 90%
“…TSA treatment in this study decreased the association between HDAC2 with the promoter region of ZO-1 as demonstrated by chromatin immunoprecipitation assay ( Ganatra et al, 2018 ). The effect of HDAC2 inhibitor CAY10683 was investigated on the expression on ZO-1 at the intestinal mucosal barrier of lipopolysaccharide (LPS)-stimulated NCM460 cells (a normal human colon mucosal epithelial cell line) ( Wang et al, 2018 ). LPS was used to induce damage to the mucosal barrier of NCM460 cells.…”
Section: Survey Methodologymentioning
confidence: 99%
“…Santacruzamate A is a selective HDAC2 inhibitor. Treatment with Santacruzamate A shows the protection of the intestinal mucosal barrier with increased expression of ZO-1 and occludin in a rat model of galactosamine/LPS-induced acute liver failure (ALF) [62]. Moreover, the treatment with Trichostatin A (TSA), a prototypical pan-HDAC inhibitor, dramatically improves intestinal permeability in the ALF rat model [63].…”
Section: Effect Of Hdac Inhibitors On the Intestinal Barrier Damaged mentioning
confidence: 99%